Critique Interdisciplinary an the Book Anthropology of Music The - Mohammad Ali Merati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article takes a critical look at Alan Merriam's book Anthropology (1923-1980), while the history of ethnomusicology considers this work as one of the foundations of the field. The knowledge of musicology and its relation to anthropology after the second half of the twentieth century is somehow gradually tied to the connection between music and Human. This article intends to examine this work in contemporary theories by considering the basic and fundamental axes of “Human Musical”. Probably, the design of some of Merriam’s principles in this book, if he were alive today, would face challenges. The process of this critique will have comparisons in the methods and ideas of comparative musicology that have been revived in the last decade or two with international music associations. But the main focus of this article is the interdisciplinary critique within the field of Ethnomusicology, which believes in the use of theories and methods more independent of the humanities or social sciences.